2022
DOI: 10.3847/1538-4357/ac6c8e
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Outward Propagating Fast-magnetosonic/Whistler Waves in the Inner Heliosphere Observed by Parker Solar Probe

Abstract: The solar wind in the inner heliosphere has been observed by Parker Solar Probe (PSP) to exhibit abundant wave activities. The cyclotron wave modes responding to ions or electrons are among the most crucial wave components. However, their origin and evolution in the inner heliosphere close to the Sun remains a mystery. Specifically, it remains unknown whether it is an emitted signal from the solar atmosphere or an eigenmode growing locally in the heliosphere due to plasma instability. To address and resolve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The SOP is inversely correlated with k B , 0 ( ) q . This indicates that the orthogonal components have a higher coherence at small propagation angles, and thus the quasi-parallel-propagating fluctuations are more wave-like (He et al 2022;Zhu et al 2023). At small propagation angles, the SOP is slightly greater at τ < 100 s than at τ > 100 s. The ellipticity distribution is isotropic at a constant period.…”
Section: Turbulent Energy Anisotropy Of Inertial-range Turbulencementioning
confidence: 95%
“…The SOP is inversely correlated with k B , 0 ( ) q . This indicates that the orthogonal components have a higher coherence at small propagation angles, and thus the quasi-parallel-propagating fluctuations are more wave-like (He et al 2022;Zhu et al 2023). At small propagation angles, the SOP is slightly greater at τ < 100 s than at τ > 100 s. The ellipticity distribution is isotropic at a constant period.…”
Section: Turbulent Energy Anisotropy Of Inertial-range Turbulencementioning
confidence: 95%
“…PSP studies show the presence of ion-scale waves, as well as significant evidence that the associated proton VDFs are prone to kinetic instability, suggesting the local growth of these waves (Verniero et al 2020;Klein et al 2021;Verniero et al 2022). A kinetic wave event in the inner heliosphere solar wind shows a clear dispersion relationship of the outward-propagating FM/W wave and a growth rate spectrum reflecting the rapid growing process of the wave event (He et al 2022). We note that Bowen et al (2020a) investigate the properties of magnetic and electric field fluctuations associated with coherent ion-scale waves.…”
Section: Introductionmentioning
confidence: 97%
“…The Parker Solar Probe (PSP) (Fox et al 2016) observations of ion-scale waves have been reported in the near-Sun plasma environment by many studies (e.g., Bowen et al 2020a;Perrone et al 2020;Verniero et al 2020;Klein et al 2021;Shi et al 2021;Zhao et al 2021b;He et al 2022). The reported ion-scale waves are often Alfvén ion cyclotron waves (ACWs) with wave frequencies around the proton gyrofrequency and kinetic Alfvén waves (KAWs) (Huang et al 2020;Duan et al 2021), which will be introduced in more detail below.…”
Section: Introductionmentioning
confidence: 99%